Studi Numerik Centrifugal Fan Tipe Impeller Backward dengan Variasi Putaran Fan - Lohdy Diana; Achmad Setiyawan; Achmad Bahrul Ulum; Arrad Ghani Safitra; Muhammad Nabiel Ariansyah (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2021)
The primary air fan functions as a primary air producer which is used as air to transport coal powder from the pulverizer to the burner to be burned in the boiler furnace. This study aims to obtain the effect of the rotation variation of fan to  fluid flow characteristics such as the distribution of total pressure, the dynamic pressure, the pressure static contours, velocity distribution, and the fan optimal efficiency. This study was numerical study with simulated a backward impeller type centrifugal fan in a two-dimension model using Fluid Computational software with the multiple reference frame method with the variation of fan rotation. Based on the visualization of the pressure contour and velocity distribution, it could be concluded that there was a volute phenomenon, this was indicated that the greater the volume area in the volute is the greater the total pressure value too. Based on the visualization of the outlet velocity distribution at the position of -0,8531m to -1,01301m, it was found that the velocity is close to the value of 0 m/s2. It showed that the minimum velocity in the area due to the volute tongue radius occurs a flow collision and it impacted the velocity in the area decreased up to V=0. From the simulation results, it was found that the greater the fan rotation value was the greater the efficiency value too. It would be verified by the actual operating data of the centrifugal fan with a minimum rotation range value of 1194 rpm to a maximum of 1468 rpm